Channel Estimation in OFDM systems: A Survey paper - Rishi, H.P.S; Behl, Garima; Kaur, Dalveer (International Journal of Computer Sciences and Engineering, 2019)
The OFDM (Orthogonal Frequency Division Multiplexing) is a modulation technique which can offer high speed voice, video and data facility up to the customer end. Developing an understanding of the Channel estimation of OFDM can be best achieved by studying two types of estimation techniques. This paper discusses the model building of channel estimation of OFDM. This model is a beneficial tool serving as a helpful reserve for the students and the scholars who want to base their studies and research in the meadow of OFDM. The performance can be enriched by using some kind of Intelligence technique. This paper also discusses the benefits of using channel estimation in an OFDM system.